PENANAMAN KEDISIPLINAN MELALUI KEGIATAN PRAMUKA SD NEGERI BATURAN 1 GAMPING SLEMAN - Ari Wibowo (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
Abstract. The research aims to find out the inculcation of discipline, as well as teacher and efforts to overcome them in instilling discipline through scout activities. The research was conducted at SDN  Baturan 1 Gamping Sleman in the 2020/2021 academic year. This study uses a qualitative method. The results showed that the incultation of discipline was carried out in a democratic way, namely by using scout clothes and attributes, inserting materials related to discipline, giving orders through hand signals or whisles, giving examples or role models, and giving reward and punisments. The obstacles faced are that there are still one or two children who are annoying, when they are explained they are busy and don’t listen, students are also influenced by the outside environment such as bad association, easy access to the internet and without supervision from parents, as well as television and magazine media. Which today are mostly uneducated. Efforts to overcome these obstacles are by getting closer to students, giving examples to students starting from using uniforms and complete attributes, advising, children, and working with parents to guide children to behave in discipline.Keywords: discipline, democracy, reward, punisment